Kepribadian Tokoh Dilan dalam Film Dilan 1990 Karya Pidi Baiq - Almas Habibati; Nur Firli Mulya; Irwan Siagian (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Literary psychology gives an important role to the character that is developed in analyzing literary works in psychological problems. In literary psychology, conflict is an upheaval between the Id, Ego, and Superego. This study aims to describe the characterizations and personalities that focus on the Id, Ego, and Superego of the main character in Pidi Baiq's Dilan 1990 film in terms of literary psychology theory. The type of research used is descriptive qualitative which analyzes the personality of the main character in the 1990 film Dilan based on Sigmund Freud's theory. Data collection techniques used in this study using observation and library techniques. The result of this research is that in the Dilan 1990 film, the main character, Dilan, is dominated by the Id and Ego elements. Dilan, who is described as a teenager in love, as well as his role as a combat commander, makes Dilan's personality very minimal with Superego.